Ni0encapsulated in N-doped carbon nanotubes for catalytic reduction of highly toxic hexavalent chromium - Yao, Y.; Zhang, J.; Chen, H.; Yu, M.; Gao, M.; Hu, Y.; Wang, Shaobin (Elsevier BV North-Holland, 2018)
© 2018 Elsevier B.V. N-doped carbon nanotubes encapsulating Ni 0 nanoparticles (Ni@N-C) were fabricated via thermal reduction of dicyandiamide and NiCl 2 ·6H 2 O, and used to remove Cr VI in polluted water. The resultant products present an excellent catalytic activity for Cr VI reduction using formic acid under relatively mild conditions. The Cr VI reduction efficiency of Ni@N-C was significantly affected by the preparation conditions including the mass of nickel salt and synthesis temperatures. The impacts of several reaction parameters, such as initial concentrations of Cr VI and formic acid, solution pH and temperatures, as well as inorganic anions in solution on Cr VI reduction efficiency were also evaluated in view of scalable industrial applications. Owing to the synergistic effects amongst tubes-coated Ni 0 , doped nitrogen, oxygen containing groups, and the configuration of carbon nanotubes, Ni@N-C catalysts exhibit excellent catalytic activity and recyclable capability for Cr VI reduction. Carbon shell can efficiently protect inner Ni 0 core and N species from corrosion and subsequent leaching, while Ni 0 endows the Ni@N-C catalysts with ferromagnetism, so that the composites can be easily separated via a permanent magnet. This study opens up an avenue for design of N-doped carbon nanotubes encapsulating Ni 0 nanoparticles with high Cr VI removal efficiency and magnetic recyclability as low-cost catalysts for industrial applications.